Analysis of Individual Knowledge of Lightning Protection - Anshori, Ibnu Fauzi; Saputra, Rizal Tri; Dikmal, Syatria Kusuma; Zul, Naufal (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2023)
The phenomenon of lightning is one of the main threats that can damage buildings and cause material losses and loss of human life Residential houses are one type of building that is vulnerable to the impact of lightning Therefore designing an effective and efficient lightning rod is very important to protect residential houses and their occupants This research aims to analyze individual knowledge related to lightning rods by looking at existing literature reviews as well as providing information about the types of lightning rods that exist and how to use them Later this research can make it easier to design a lightning rod system that is suitable for residential houses by considering the safety and comfort of the occupants In this research we conducted a survey and analysis of scientific articles books and other reliable sources relevant to individual knowledge about lightning rods This research will include an understanding of the working principle of lightning risk assessment of residential houses selection of the right type of lightning rod and selection of suitable materials for lightning rod systems The research method used is interviews with residential homeowners This interview was conducted to obtain information regarding their experience and knowledge about lightning rods Based on the results of interviews with residential homeowners who do not install lightning rods it can be concluded that an effective lightning rod must consider factors such as the specific needs of the residence environmental characteristics and local weather conditions The selection of < p>